Experiments and modelling of NOx precursors release (NH3 and HCN) in fixed-bed biomass combustion conditions. (15th June 2018) - Anca-Couce, Andrés; Sommersacher, Peter; Evic, Nikola; Mehrabian, Ramin; Scharler, Robert
Highlights: Release of N-species investigated for 32 biomass types in a fixed-bed reactor. The NH3 /HCN ratio increases for fuels with a higher nitrogen content. Presented a simplified two-steps model for the release of NOx precursors. Good predictions for fuels with a low nitrogen content. Deviations for fuels with a high nitrogen content due to reduction in the bed. Abstract: There is a need to reduce NOx emissions, which can only be achieved through a detailed understanding of the mechanisms for their formation and reduction. In this work the release of the NOx precursors, NH3 and HCN, for different fuels is experimentally analysed and modelled in typical fixed-bed combustion conditions. It is shown that NH3 and HCN are released during the main devolatilization phase and the NH3 /HCN ratio increases for fuels with a higher nitrogen content. A simplified two-steps model for their release is presented. The model can predict with a reasonable accuracy the release for fuels with a low nitrogen content, however deviations are present for fuels with a high nitrogen content, which probably arise due to a reduction of NH3 and HCN taking place already in the bed.